(untitled) (MAUSAM, 1982)
Mean absolute angular momentum and its transport associated with monsoon depressions have been discussed in the paper. For the purpose of this study, depressions which formed in two representative monsoon months of July & August between 1961 & 1974 and moved In the customary west or westnorthwest direction have been pooled to obtain a generalised portrayal of the expected accumulation of the momentum throughout the troposphere, around 1000 km of the depression centre. Estimates have been made of the surface stress by means of which the angular momentum are transferred. Empirical relationship between the drag coefficients and the wind has been deduced. The study reveals that the air which penetrates deep inside the depression field loses maximum momentum in the lower levels while in the upper troposphere angular momentum is generally conserved. Maximum extraction of momentum is found to occur in the high velocity core of the depression. The nature of relationship between the surface drag and the wind is found to be quadratic. Relatively uniform angle of inflow is observed near the depression centre.